OFFF Festival 2025 International Festival of Art, Creativity, and Digital Design - Panayides, Angelos (My University, 2026)
The 25th edition of OFFF, an internationally recognised festival for creativity, art, and digital design, was held from May 8th to 10th at Disseny Hub Barcelona. The venue was transformed into a multidisciplinary platform for critical engagement with contemporary practices in design, motion, artificial intelligence, and digital culture. The festival convened over 70 international speakers, practitioners, and studios contributing to current discourse in the field. The programme comprised keynote lectures, curated talks, workshops, and specialised sessions delivered by leading figures and studios, including DixonBaxi, Marina Willer, Mat Voyce, Ines Alpha, and Territory Studio. The event facilitated knowledge exchange, professional development, and interdisciplinary dialogue, fostering engagement between established practitioners, emerging creatives, and students. Across the three-day programme, OFFF 2025 hosted over 70 talks and more than 20 workshops and masterclasses. Additional activities included presentations of emerging design tools, a curated design market, and informal networking environments. The festival concluded as a significant academic and professional gathering, reinforcing OFFF’s role in shaping contemporary and future-oriented design practice.